Building markets for knowledge resources - Della Peruta, Maria Rosaria (Innovation, technology, and education for growth., 2016)
Peruta examines emerging pervasive models of innovation and how their nature, effects, and origins are characterized. The book starts with the definition of markets for knowledge resources and analyses the integration of market players (e.g. suppliers, customers, competitors, laboratories and research institute) such as the fundamental prerequisite for promoting the development of the new era of open innovation. By focusing on different organizational models and considering both mechanisms pecuniary and non-pecuniary, the book aims to compare the theoretical assumptions and the managerial implications of the emerging open business models with the traditional closed innovation ones. The open business models are characterized essentially by the fact of encouraging innovation as part of the interactive co-creation process outside the boundaries of the firm.